Exponential Stability for a Bresse System with Hybrid Dissipation - Araújo, Rawlilson O. [UNESP] (Springer Nature, 2023)
A new Bresse system with hybrid damping coming from elasticity, thermoelasticity, and viscoelasticity, is analyzed. The uniform (exponential) stabilization of semigroup solution is proved under the dynamic response of each hybrid damping effect.
Keywords: Bresse system; Elasticity; Exponential stability; Hybrid damping; Thermoelasticity; Viscoelasticity